Implementation of the Prolanis Online Health Service Management Information System Application (SIMPELPRO) at the Semarang City Public Health Center , Case Study at Padangsari Public Health Center Semarang City - Setya - Wijayanta; Siti Masrochah; Subinarto Subinarto; Indah Naryanti (Poltekkes Kemenkes Semarang, 2023)
The government is working to reduce the prevalence of chronic diseases and prevent people with chronic diseases from entering the complication stage. One form of effort in this regard is through the chronic disease management program (Prolanis). So that the participants do not know the types of activities and schedules of Prolanis activities so that participants do not take advantage of them. The purpose of this study was to examine the implementation of the online prolanis service management information system application (SIMPELPRO) at the Semarang City Public Health Center, a case study at the Padangsari Public Health Center. This research method is descriptive, with primary data sources from interviews, documentation studies and literature. System design using the prototype method. Prototypes were made and evaluated, and continued to the implementation stage. The result of this study Has been developed using SIMPELPRO web based application for service management of Prolanis activities. The focus of the application in this research is still on the presentation of the health education materials. The development uses the prototype method with UML as a design tool. The application has received positives feedbacks from Prolanis participants, Although some participants have complainedabout limited access to smartphones and the need for assistance for elderly participants.